2017
DOI: 10.1016/j.ejrad.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of radiation protection and dose levels of imaging procedures among medical students, radiography students, and radiology residents at an academic hospital: Results of a comprehensive survey

Abstract: Radiology residents, radiography students and medical students have a limited awareness about radiation protection, with a specific gap of knowledge concerning real radiation doses of daily radiological examinations. Both undergraduate and postgraduate teaching needs to be effectively implemented with radiation safety courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 27 publications
7
63
1
1
Order By: Relevance
“…This study, like Zhou et al (2010) and Dellie et al (2015) found that students who reported moderate confidence in their knowledge, scored better than those who were not confident with their knowledge [ 3 , 14 ]. The present study finding is inconsistent with the earlier study [ 15 ] that identified that there was a negative relationship between students confidence and radiation related knowledge and that students who reported moderate confidence in their knowledge on radiation related knowledge scored lower scores in objective tests.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This study, like Zhou et al (2010) and Dellie et al (2015) found that students who reported moderate confidence in their knowledge, scored better than those who were not confident with their knowledge [ 3 , 14 ]. The present study finding is inconsistent with the earlier study [ 15 ] that identified that there was a negative relationship between students confidence and radiation related knowledge and that students who reported moderate confidence in their knowledge on radiation related knowledge scored lower scores in objective tests.…”
Section: Discussioncontrasting
confidence: 99%
“…These results support the hypothesis that medical students are not aware of radiation doses and its associated risks for commonly performed diagnostic imaging procedures. The findings of this study are consistent with those of previous studies that also report poor knowledge of ionising radiation procedures amongst medical students [ 3 , 15 – 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A study by Faggioni et al found that people with less radiation knowledge had higher selfesteem. This issue led to poor self-esteem among medical students, which may be one of the psychological factors for inattention to learn about the subject of radiation knowledge (36). L.Borgen and his colleagues have found that radiology experts and residents have more radiation and shielding information from physicians due to the specialized nature of their units, which con rms our results (19).…”
Section: Discussionsupporting
confidence: 79%
“…A study by Rahman et al in Pakistan in 2008 on cardiovascular specialists during angiography and its protection showed that 93% of the sample knew about lead shields and used lead coveralls (21). A recent study in Italy showed that the knowledge of radiology specialists, radiology students, and medical students is limited with regards to protection from ionizing radiation (22). One important point to note here is that informing parents of the harms and risks of diagnostic imaging before performing tests on their children, should be considered ethically and legally.…”
Section: Discussionmentioning
confidence: 99%